From Pailis to pasungko negotiating the present, ascertaining the future (indigenous knowledge systems and opportunities for biodiversity management and conservation) - Castro, Luz C. Sevidal; Viloria, Liwayway S.; Hanasan, Johanna E.; Bago, Raymundo T. (2006)
This study describes the indigenous knowledge systems, the adaptive strategies, and the traditional resource use practices of the Subanun in Mt. Malindang. The study sites included six (6) communities located in the province of Misamis Occidental. It benefited from a triangulation of methods and sources: documentary review and secondary data gathering: focus group discussion; key informant interviews and testimonies, participant and non-participant observation.

Similar to many indigenous peoples in the Philippines, the Subanun have lived with the vicissitudes of their biophysical environment for ages, moving through river systems, across hills and over mountains that punctuate the landscape of their ecosystem. Central to their culture is the belief that human beings are stewards of the vast resources in their surroundings. In the utilization of these resources, they observe certain cultural prescriptions and proscriptions. The Subanun indigenous knowledge system (IKS) has undergone transformations through time, as evidenced in the syncretic nature of their adaptive strategies (knowledge, techniques, beliefs and practices). Such transformations are contexted in the circumstances - environmental changes, social pressures, market-driven economy and constraints imposed by law impinging on their interactions with the biophysical environment and various stakeholders.

The traditional practices are a function of the need for survival. Several elements of Subanun IKS exercise regulatory functions in resource use. Among these elements are: sal-ang; pamuhat; terracing; use of indigenous materials for fertilizer; paanuton/pasagbutan, or fallowing. An appreciation of the ways in which IKS elements prevent over-exploitation or deterioration is essential in biodiversity management and conservation of the ecosystems in the study sites. These IKS elements may synergize with approaches that are based on formalscience and modern technology, articulated in various ways that, while assuming a pragmatism that is cognizant of the demands and pressures of the biophysical, socio-economic environment, are also capable of protecting the natural resource base of the environment. Such lessons provide inputs for designing cultural and biological diversity conservation and development programs at the local and national scales.
Keywords: Indigenous knowledge, systems and practices; Indigenous peoples -- Mindanao; Subanuns; Subanen